Peranan Bank Syariah Indonesia dalam Memajukan Sektor Industri Makanan Halal - Warto, Warto; Nurlaila, Lala; Khumaini, Sabik (Al Maal: Journal of Islamic Economics and Banking, 2024)
This research aims to determine the role of Indonesian Sharia Banking in advancing the halal food industry in Indonesia and determine the types of financing products used. This research is descriptive qualitative in nature, the data sources the author uses are primary and secondary data. Data collection was carried out by means of observation, interviews, literature study and documentation. The results of this research show that Bank Syariah Indonesia plays a role in developing the halal food industry in Indonesia through; (a) KUR financing products, namely BSI KUR Micro and BSI KUR Small. This funding also supports the development of halal food businesses for micro-entrepreneurs in the Tangerang Balaraja area. (b) Human Resources Development. These two products play a crucial role in advancing the halal food industry in the area and contributing to improving the economy of their customers. However, BSI KCP Tangerang Balaraja needs to supervise the use of financing so that it is actually used for business capital needs and not for consumtive needs.